The Filtering System Modification on Rainwater Harvesting Technology with Centrifugal System for Reduce TDS - Riki Chandra Wijaya; Siti Nutul Khotimah (Research Centre of Inorganic Materials and Complexs, 2021)
Rainwater harvesting technology is needed today. The development fast that occurs has the impact of increasing the use ground water. Rainwater harvesting technology is the main solution in this case. Apart from being a water source, it can also restore the groundwater level to its original condition. Rainwater harvesting technology currently still needs a lot of development in order to produce better rainwater quality. For this reason, in this study modifications will be made to the initial filter to separate the initial sediment from pure rainwater when it rains. The centrifugal system in this case will be used to take part in separating sediment from rainwater. Centrifugal filtration systems are made using several tools and easily available materials. Based on the results of this study, it is known that the level of TDS reduction from before the use of centrifugal filters to after use is 62.2%. This decrease can be seen from the TDS value before the use of an average of 12.2, while after the use centrifugal filter the average TDS is 4.6.